2006
DOI: 10.1016/j.actpsy.2005.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual and perceptual memory: Retrieval orientations reflected in event-related potentials

Abstract: In memory retrieval, search can be guided by mental sets towards diVerent subsets of the available evidence. Such retrieval orientations have been suggested to leave an imprint on event-related potentials (ERPs). The present study aimed at characterizing orientations towards perceptual and conceptual evidence in a recognition task, where pictures and words were studied. In the recognition test, items were presented in either the same format as at study or in the opposite format. A between-subjects manipulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 55 publications
7
24
1
Order By: Relevance
“…Greater positive amplitudes were observed for repeated faces (old target and old nontarget) than for new ones, confirming that the parietal old-new effect reflects the implementation of controlled memory processes related to the retrieval of contextual details or associative information (Curran and Hancock, 2007;Senkfor and Van Petten, 1998;Stenberg et al, 2006), even on an exclusion task (Bridson et al, 2006;Guillaume and Tiberghien, 2013). This outcome extends previous findings indicating that the posterior modulation is not simply sensitive to repetition but should be linked to explicit memory processes during face recognition (Guillaume and Tiberghien, 2013;MacKenzie and Donaldson, 2007;Yick and Wilding, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…Greater positive amplitudes were observed for repeated faces (old target and old nontarget) than for new ones, confirming that the parietal old-new effect reflects the implementation of controlled memory processes related to the retrieval of contextual details or associative information (Curran and Hancock, 2007;Senkfor and Van Petten, 1998;Stenberg et al, 2006), even on an exclusion task (Bridson et al, 2006;Guillaume and Tiberghien, 2013). This outcome extends previous findings indicating that the posterior modulation is not simply sensitive to repetition but should be linked to explicit memory processes during face recognition (Guillaume and Tiberghien, 2013;MacKenzie and Donaldson, 2007;Yick and Wilding, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…Previous retrieval orientation studies showed more negative ERPs to new items in conditions that were characterized by incongruent study and test formats (e.g. pictures and words), as compared to conditions in which study and test formats were the same (Halsband, Ferdinand, Bridger, & Mecklinger, 2012;Herron & Rugg, 2003;Hornberger, Morcom, & Rugg, 2004;Robb & Rugg, 2002;Stenberg, Johansson, & Rosén, 2006). It has been suggested that the more negative ERPs in case of study-test incongruence reflect processing differences necessary to maximize overlap between cue and memory representations; in particular, the differential reliance on semantic/conceptual information derived from retrieval cues was proposed to play a major role (Hornberger et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Rugg and colleagues have shown that ERPs to new items in recognition tests vary depending on whether the participants attempt to remember pictures or words from the study phase. These effects take the form of more negative ERPs for test cues that are physically dissimilar from the sought-after information, and are evident over a broad region of the scalp (Herron and Rugg, 2004;Hornberger et al, 2004;Robb and Rugg, 2002; see also Stenberg et al, 2006). These studies suggest that the retrieval of specific varieties of information from an episode is subject to a fair degree of voluntary control, such that test cues undergo differential processing depending on the specific demands of the memory test.…”
Section: Retrieval Orientationmentioning
confidence: 99%
“…In a general sense, these negative potentials might reflect the processes required to convert a physical test cue into an internal format more closely aligned with the information sought in memory. If this interpretation is correct, one would expect the scalp topography and wave-shape of retrieval orientation effects to vary somewhat depending on the nature of the initial format (the physical cue) and the target format (the internal retrieval cue), as observed in some of these prior studies using words and pictures (Hornberger et al, 2004;Stenberg et al, 2006). By this perspective, there is no single "retrieval orientation effect", but rather a set of processes that help to align test cues with stored information.…”
Section: Orienting Retrieval To Item Versus Source Informationmentioning
confidence: 99%